2021
DOI: 10.1186/s12934-020-01490-2
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing and metabolomics analyses reveal the biosynthesis of nerol in a multi-stress-tolerant Meyerozyma guilliermondii GXDK6

Abstract: Background Nerol (C10H18O), an acyclic monoterpene, naturally presents in plant essential oils, and is used widely in food, cosmetics and pharmaceuticals as the valuable fragrance. Meanwhile, chemical synthesis is the only strategy for large-scale production of nerol, and the disadvantages of chemical synthesis greatly limit the production and its application. These defects drive the interests of researchers shift to the production of nerol by eco-friendly methods known as biosynthesis methods.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…Whole-genome sequence analysis showed that the total bases of GXDK6 were 2,477,073,673 bps, and its GC content accounted for 38.88%. The genome sequencing data were deposited to the National Microbiology Data Center database (http://nmdc.cn) under accession number NMDC60014229 (14). Compared genomic analysis showed that 14 genes (Table 1) related to salt tolerance were annotated, suggesting that GXDK6 is a high salt-tolerant strain, well consistent with the results shown in Fig.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Whole-genome sequence analysis showed that the total bases of GXDK6 were 2,477,073,673 bps, and its GC content accounted for 38.88%. The genome sequencing data were deposited to the National Microbiology Data Center database (http://nmdc.cn) under accession number NMDC60014229 (14). Compared genomic analysis showed that 14 genes (Table 1) related to salt tolerance were annotated, suggesting that GXDK6 is a high salt-tolerant strain, well consistent with the results shown in Fig.…”
Section: Resultssupporting
confidence: 79%
“…1, GXDK6 was isolated from the subtropical marine mangrove sediments in the Beibu Gulf of China; its physicochemical characteristics were identified in previous studies (Figs. 1a-c) (14). The results showed that GXDK6 could continuously grow under a concentration of 0%-1% NaCl, indicating high salt tolerance (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Therefore, microorganisms with multiple stress tolerance and good heavy metal removal have gained interests. A previous study identified the multi stress tolerant yeast Meyerozyma guilliermondii GXDK6 with aroma-producing properties from subtropical marine mangrove wetland microorganisms ( Mo et al, 2021 ). This species can survive 1400 ppm (22 mM) copper ions, which is the highest tolerance concentration reported to date.…”
Section: Introductionmentioning
confidence: 99%